Antioxidants - Shalaby, Emad (Physiology, 2019)
Antioxidants are substances that can prevent or slow damage to living cells caused by free radicals, which are unstable molecules the body produces as a reaction to environmental and other pressures. Sometimes called "free-radical scavengers," free radicals can cause mutation in different biological compounds such as protein, nucleic acids, and lipids, which lead to various diseases (cancer, cardiovascular disease, aging, etc.). Healthy foods are considered a main source of antioxidant compounds and from the beginning of a person's life, a strong relationship is seen between antioxidant compounds and the prevention of certain diseases, such as types of inflammations, cardiovascular diseases, and different kinds of cancers. It is thus of great importance that new data relating to antioxidants and their biological activity be collected and that antioxidant modes of action be illustrated.Experts from around the world contributed to the current book, discussing antioxidant sources, modes of action, and their relation to human diseases. Twenty-five chapters are presented in two sections: Antioxidants: Sources and Modes of Action and Antioxidants Compounds and Diseases.